Power of photonic states: from computation to cosmology - Liu, N (2016)
This thesis is an exploration of the power of photonic resources, as viewed from several different but related perspectives. They range from quantum computation, precision parameter estimation to the thermodynamics of relativistic quantum systems, as applied to cosmology in particular. The use of photonic states allows us to address several important questions about the resources required in quantum mechanical processes. In chapter 1, we propose a new quantum computational model, called the `power of one qumode', that relies mainly on a single-mode photonic squeezed state. In particular, we show the amount of squeezing can quantitatively relate the resource requirements of factoring to the problem of finding the trace of large unitary matrices, a result with consequences for understanding how powerful quantum computation really is. Furthermore, we can connect squeezing to other known resources like precision, energy, qudit dimensionality and qubit number, which is a useful stepping stone to finding the resources that enable quantum computation. In chapter 2, we exploit the quantum mechanical properties of photonic states for use in precision parameter estimation of general linear optical processes, which is useful for a diverse number of applications, from characterising an unknown process in a photonic quantum computer to biological imaging. We introduce a formalism that quantifies this improvement in precision. We also provide conditions under which one can easily check for photonic states that are optimal to use in this context, which is a potentially important result for future experimental efforts. In chapter 3, we explore the connection between two-mode squeezed states, commonly used in quantum optics, and relativistic quantum processes, in particular in cosmology. Using this connection, we apply recently developed tools from the thermodynamics of quantum systems perturbed far from equilibrium to address an old question of entropy production in cosmology from a surprising new angle.